2007
DOI: 10.1097/01.pai.0000213107.20355.d8
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-methylacyl-CoA Racemase/P504S Overexpression in Colorectal Carcinoma is Correlated With Tumor Differentiation

Abstract: Alpha-methylacyl-CoA racemase (AMACR)/P504S is an enzyme involved in the metabolism of branched-chain fatty acids. Little is known about correlation of AMACR expression with colorectal carcinoma (CRC) differentiation and prognosis. We investigated the expression of AMACR in 106 cases of primary CRC, and in 47 lymph nodes with metastatic CRC by immunohistochemical analysis. These cases were divided into 3 groups according to the histologic differentiation of the primary tumors. group A included 50 cases of hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
1
9
1
2
Order By: Relevance
“…Other investigators described 45% to 83% AMACR positive CRC, but all of these studies were performed on patient numbers smaller than 200 [2,8,13,20,25,27,30]. The association found with non-mucinous tumor type, tumor grade, and tumor stage was also in line with the results of a previous study [13].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Other investigators described 45% to 83% AMACR positive CRC, but all of these studies were performed on patient numbers smaller than 200 [2,8,13,20,25,27,30]. The association found with non-mucinous tumor type, tumor grade, and tumor stage was also in line with the results of a previous study [13].…”
Section: Discussionsupporting
confidence: 80%
“…Comparable to Shi et al, no significant association between AMACR expression and prognosis could be found in our study, despite other features such as tumor grade and tumor stage which were highly significant for the outcome in this patient cohort [25]. However, the differences in AMACR expression between tumors of different grade and stage were quite small in terms of absolute numbers.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…and immunohistochemical expression of classic renal markers (Table 6). It is of importance to stress that AMACR has no specificity for renal primaries and it is expressed in many adenocarcinomas of other origins, for example prostatic, gastric, or colorectal [41,42]. The most common primary sites are lung, breast, skin a b c Fig.…”
Section: Metastatic Carcinomamentioning
confidence: 99%